A new tidal analysis of superconducting gravity observations in Western and Central Europe - HÁBEL, Branislav; MEURERS, Bruno (Contributions to Geophysics and Geodesy, 2014)
Tidal analysis was applied on 1 hour gravity data acquired by a subnet of 12 superconducting gravimeters situated in western and central parts of Europe. Tidal parameters for O1 and M2 were adjusted. Most of the gravity time series were provided by the Global geodynamics project. Filter effects of the decimation process were carefully studied and taken into account where necessary. The ocean loading effect included in observed tidal parameters was removed using 8 ocean models with different spatial resolutions. Two different comparisons of corrected tidal parameters were performed. As a result, the accuracy of ocean loading correction and global calibration error were evaluated. For O1, amplitude factors are in good agreement with the hydrostatic/elastic model DDW/He while the non-hydrostatic/inelastic model DDW/NHi better describes the M2 amplitude factors. The analysis of residual vectors allowed assessing the efficiency of the used ocean loading models which is about 81% (O1) and 97% (M2).